A Study On Service Quality And Customer Satisfaction To Enhance Loyalty At PT Bpr Syariah Harta Insan Karimah - Muhammad Furqon; Marlina Marlina; Lilis Suharti; Leonita Maharani; Siti Komala (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This research was conducted to measure the influence of service quality and customer satisfaction on enhancing customer loyalty at PT BPR Syariah Harta Insan Karimah. In this study, service quality and customer satisfaction serve as independent variables, while customer loyalty is the dependent variable. A quantitative research method was applied, utilizing purposive sampling to select 100 respondents who met specific criteria relevant to the study's objectives. Data collection was carried out through structured questionnaires based on established indicators for each variable. To analyze the data, multiple linear regression analysis was used to evaluate both the simultaneous and partial effects of the independent variables on customer loyalty. The results reveal that service quality and customer satisfaction together have a positive and significant effect on customer loyalty, suggesting that a combination of excellent service and high customer satisfaction contributes to strengthening customer relationships. However, when examined individually, only service quality was found to have a significant and positive impact on customer loyalty, while customer satisfaction did not show a significant influence. This implies that while satisfaction is important, the quality of service plays a more dominant role in fostering loyalty among customers. The findings underscore the strategic importance of consistently delivering high service quality to build long-term customer relationships and sustain competitive advantage in the banking sector.